Intra- and extracellular events in luminol-dependent chemiluminescence of polymorphonuclear leukocytes. - Briheim, G (1984)
When polymorphonuclear leukocytes (PMNL) and soluble or particulate matter interact, the cells produce chemiluminescence. Luminol-dependent light emission from PMNL is linked to the myeloperoxidase (MPO)-H2O2 system. Light emission from a cell-free MPO-H2O2 system was found to be totally inhibited by human serum albumin (HSA), and since HSA is a large molecular protein that does not readily gain access to intracellular sites of PMNL, it could be used to determine the importance of extra- and intracellular events in PMNL chemiluminescence. In studies with cells from an MPO-deficient patient, we found that HSA inhibited more than 90% of extracellularly produced chemiluminescence. The chemotactic peptide formylmethionyl-leucyl-phenylalanine induced a two-peak chemiluminescence response in normal PMNL, and addition of HSA reduced the first peak, whereas the second peak was unaffected. This result indicated that the first peak was a result of extracellular reactions and the second peak was a result of intracellular reactions of the MPO-H2O2 system. Most of the phorbol myristate acetate-induced response in normal PMNL was due to intracellular events. Furthermore, chemiluminescence of intracellular origin seems to be limited not by generation of oxidative metabolites but by diffusion of luminol into the cells.